Influence of equal channel angular pressing on the properties of polylactic acid. Issue 5 (19th April 2017) - Li, Hong; Wu, Zhemin; Xue, Feng; Bai, Jing; Chu, Chenglin
Abstract : The effects of equal channel angular pressing (ECAP) on the microstructures, mechanical, and degradation properties of polylactic acid (PLA) were investigated. The controllable microstructures of PLA can be achieved by a 3D rotary‐die through various combinations of passes and routes (A′ and C′). For A′ route, sample was extruded sequentially through four channels in a plane with compressive or tensile stress alternatively imposed on the two major load bearing surfaces, while for C′ route, sample was extruded only in two vertical channels back and forth with constant compressive or tensile stress imposed on the two major load bearing surfaces. The strong preferential orientation of (200) plane parallelled to the axis direction was formed under the conditions of A′ route for two passes and C′ route for three passes. There was a more uniform distribution in the microhardness for the sample extruded by two passes under C′ route. Meanwhile the sample had higher bending strength after two passes under A′ route, and better facture toughness after three passes under C′ route. The reductions in mass and bending strength of PLA processed by ECAP were more obvious than those of original sample in phosphate‐buffered solution at 37°C for 16 weeks. POLYM. ENG. SCI., 2017. © 2017 Society of Plastics Engineers